Conditional Performance Evaluation for German Mutual Equity Funds - Wolfgang Bessler; Wolfgang Drobetz; Heinz Zimmermann (University of Basel, Center of Business and Economics (WWZ), 2007)
We investigate the performance of a sample of German mutual equity funds over the period from 1994 to 2003. Our general finding is that mutual funds, on average, hardly produce excess returns relative to their benchmark that are large enough to cover their expenses. This conclusion is drawn from a variety of model specifications and is robust to many different benchmarks. Compared to unconditional measures, fund performance substantially deteriorates when we measure conditional alphas both in single-index and multi-factor models. We also measure fund performance in the Euler-equation framework and test several specifications of the stochastic discount factor using GMM. The result that funds underperform even before costs is even more pronounced. Overall, given the fact that stock returns are to some extent predictable by using publicly available information, conditional analysis raises the hurdle for active managers seeking abnormal positive performance, because it gives them no credit for exploiting readily available information.
Keywords: 330; Mutual funds; stock return predictability; conditional performance measurement; stochastic discount factor; Kapitaleinkommen; Investmentfonds; Prognoseverfahren; Performance-Messung; Schätzung; Deutschland